2015
DOI: 10.1371/journal.pone.0115552
|View full text |Cite
|
Sign up to set email alerts
|

Using a Partial Sum Method and GPS Tracking Data to Identify Area Restricted Search by Artisanal Fishers at Moored Fish Aggregating Devices in the Commonwealth of Dominica

Abstract: Foragers must often travel from a central place to exploit aggregations of prey. These patches can be identified behaviorally when a forager shifts from travel to area restricted search, identified by a decrease in speed and an increase in sinuosity of movement. Faster, more directed movement is associated with travel. Differentiating foraging behavior at patches from travel to patches is important for a variety of research questions and has now been made easier by the advent of small, GPS devices that can tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…Like in other cases (Daw et al, 2011;Alvard et al, 2015;Metcalfe et al, 2016), the map obtained in this study (Figure 3) clearly shows that fishing effort is not evenly distributed in the area around Badi but focused on specific fishing grounds. This type of information can be useful for spatial zonation for management planning, but should be complemented with GPS tracking data from other islands and seasons, and combined with knowledge of the informal institutions ruling the access to these fishing grounds (Deswandi, 2012;Gorris, 2016).…”
Section: Mapping Fishing Effort Allocationsupporting
confidence: 76%
See 3 more Smart Citations
“…Like in other cases (Daw et al, 2011;Alvard et al, 2015;Metcalfe et al, 2016), the map obtained in this study (Figure 3) clearly shows that fishing effort is not evenly distributed in the area around Badi but focused on specific fishing grounds. This type of information can be useful for spatial zonation for management planning, but should be complemented with GPS tracking data from other islands and seasons, and combined with knowledge of the informal institutions ruling the access to these fishing grounds (Deswandi, 2012;Gorris, 2016).…”
Section: Mapping Fishing Effort Allocationsupporting
confidence: 76%
“…Another reason to include traditional interview methods in boat tracking studies is that artisanal fisheries are very diverse, and GPS setting up and data processing may require different configurations. For instance, Alvard et al (2015) worked with hand-line fishermen in Dominica, and identified three speed ranges far above the ones described in this study (Table 5), probably because in that case the boats had more powerful engines, and perhaps also for differences in the behavior of target species because they target tuna (Scombridae), marlin (Istiophoridae), and dolphinfishes (Coryphaenidae) that swim faster than the groupers. Therefore, research plans should still include procedures to characterize the fishing gears and fishermen's knowledge on how to use them.…”
Section: Identification Of Fishing Grounds In Multi-gear Artisanal Fimentioning
confidence: 63%
See 2 more Smart Citations
“…Our work shows that these data are important when exploring how mature stock attributes may manifest in such populations and, consequently, that such data is needed to better inform managers whose goal is the preservation of these fish stocks. Advances in GPS (global positioning satellite) technology capable of precisely documenting catch by latitude and longitude and the increase in vessels utilizing this technology provide promising potential solutions to solving this dilemma (Omar and Hassan, 2011;Gutowsky et al, 2013;Alvard et al, 2015). Data from tagging experiments may also be used to estimate movement rates (Hampton, 1991;Arregui et al, 2006;Kurota et al, 2009) and substock structure (Block et al, 2005).…”
Section: Data Considerationsmentioning
confidence: 99%